2010
DOI: 10.1007/s10096-010-1007-y
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo activities of linezolid alone and combined with vancomycin and imipenem against Staphylococcus aureus with reduced susceptibility to glycopeptides

Abstract: The objective of this study was to evaluate the in vitro and in vivo efficacies of linezolid (35 mg/kg/5 h), vancomycin (60 mg/kg/5 h), imipenem (30 mg/kg/5 h), linezolid+imipenem, linezolid+vancomycin and vancomycin+imipenem against two clinical Staphylococcus aureus isolates with reduced susceptibility to glycopeptides using time–kill curves and the murine peritonitis model. Time–kill curves were performed over 24 h. For the murine peritonitis model, peritonitis was induced by the intraperitoneal inoculation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 32 publications
0
22
0
2
Order By: Relevance
“…At least 16 in vitro studies have explored synergy between vancomycin and β-lactams against MRSA isolates, [54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69] all but one of which found evidence of synergy in some or all of the tested strains (►Table 1). These studies varied in their methodology (checkerboard synergy testing or time-kill curves), types of strains tested (MRSA vs. hVISA vs. VISA) and the β-lactams used, but a consistent finding across nearly all the studies was synergistic bacterial killing in most but not all strains tested.…”
Section: In Vitro Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…At least 16 in vitro studies have explored synergy between vancomycin and β-lactams against MRSA isolates, [54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69] all but one of which found evidence of synergy in some or all of the tested strains (►Table 1). These studies varied in their methodology (checkerboard synergy testing or time-kill curves), types of strains tested (MRSA vs. hVISA vs. VISA) and the β-lactams used, but a consistent finding across nearly all the studies was synergistic bacterial killing in most but not all strains tested.…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…The few studies that have assessed combinations of vancomycin with β-lactams in animal models have all found evidence of synergy. 56,61,65 Climo et al found faster sterilization of infection with vancomycin plus nafcillin in MRSA rabbit endocarditis and renal abscess models. 56 Ribes et al tested various combinations of linezolid, vancomycin, and imipenem in a murine peritonitis VISA model using time-kill curves, and found faster bacterial killing with vancomycin plus imipenem compared with vancomycin alone, in both strains tested.…”
Section: Animal Studiesmentioning
confidence: 99%
“…The combination of antibiotics acting by different mechanisms is recommended for the treatment of MRSA infections in order to ensure a synergistic action, reduce the occurrence of side-effects, and decrease the risk of resistance. These different antibiotic combinations offer a potential option in the management of the infections caused by MRSA (9)(10)(11)(12)(13)(14). In our study, the E test method was used to evaluate the synergistic effects of the antibiotics against MRSA strains isolated from patients in intensive care units.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative therapies including novel combinations are essential to treat MRSA infections. Different antibiotic combinations are frequently used for the treatment of infections caused by MRSA strains (9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Linezolid has unique mechanism of action by inhibiting ribosomal protein synthesis at an early stage of bacterial replication which leads to the absence of cross resistance with other antimicrobials (Rubinstein et al, 2010). Although linezolid unsusceptible strains are unusual, long courses of oxazolidinone therapy could select resistant mutants (Wilson et al, 2003) hence, the use of a combined strategy might be considered in clinical practice (Ribes et al, 2010). Combination therapy, with the goal to enhance the antibacterial activity of known and effective antibiotics, cannot only enhance the activity of known antibiotics but can possibly support the clinical development of agents previously found to be very effective but too toxic for the host.…”
Section: Discussionmentioning
confidence: 99%